The 2015 IUIS Phenotypic Classification for Primary Immunodeficiencies (2015)
ABSTRACT: There are now nearly 300 single-gene inborn errors of immunity underlying phenotypes as diverse as infection, malignancy, allergy, auto-immunity, and auto-inflammation. For each of these five categories, a growing variety of phenotypes are ascribed to Primary Immunodeficiency Diseases (PID), making PIDs a rapidly expanding field of medicine. The International Union of Immunological Societies (IUIS) PID expert committee (EC) has published every other year a classification of these disorders into tables, defined by shared pathogenesis and/or clinical consequences. In 2013, the IUIS committee also proposed a more user-friendly, phenotypic classification, based on the selection of key phenotypes at the bedside. We herein propose the revised figures, based on the accompanying 2015 IUIS PID EC classification.